Deciphering the contributing motifs of reconstructed cobalt (II) sulfides catalysts in Li-CO2 batteries - Yingqi Liu; Zhiyuan Zhang; Junyang Tan; Biao Chen; Bingyi Lu; Rui Mao; Bilu Liu; Dashuai Wang; Guangmin Zhou; Hui-Ming Cheng (Nature Communications, 2024)
Abstract Developing highly efficient catalysts is significant for Li-CO2 batteries. However, understanding the exact structure of catalysts during battery operation remains a challenge, which hampers knowledge-driven optimization. Here we use X-ray absorption spectroscopy to probe the reconstruction of CoSx (x = 8/9, 1.097, and 2) pre-catalysts and identify the local geometric ligand environment of cobalt during cycling in the Li-CO2 batteries. We find that different oxidized states after reconstruction are decisive to battery performance. Specifically, complete oxidation on CoS1.097 and Co9S8 leads to electrochemical performance deterioration, while oxidation on CoS2 terminates with Co-S4-O2 motifs, leading to improved activity. Density functional theory calculations show that partial oxidation contributes to charge redistributions on cobalt and thus facilitates the catalytic ability. Together, the spectroscopic and electrochemical results provide valuable insight into the structural evolution during cycling and the structure-activity relationship in the electrocatalyst study of Li-CO2 batteries.